2011
DOI: 10.3109/09638288.2011.579224
|View full text |Cite
|
Sign up to set email alerts
|

Returning to work after spinal cord injury: exploring young adults' early expectations and experience

Abstract: The participants represent a vulnerable group in vocational rehabilitation due to their young age and recent injury. Without formal training or suitable work experience, they need tailored work support as part of their general rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 17 publications
2
48
0
Order By: Relevance
“…16 Similarly, a Swedish study of young adults aged 20-34 who had sustained a SCI indicated that this population perceived themselves as ready to and capable of work, but required guidance in making vocational decisions and support in sourcing appropriate work experience or training. 7 Those who do return to work early tend to return to their previous employer, 16 and supportive employers have been recognised as promoting employment in this population. 24 Early vocational intervention could preserve this relationship and maximise employer support through liaison with the employer and use of appropriate workplace supports.…”
Section: Early Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Similarly, a Swedish study of young adults aged 20-34 who had sustained a SCI indicated that this population perceived themselves as ready to and capable of work, but required guidance in making vocational decisions and support in sourcing appropriate work experience or training. 7 Those who do return to work early tend to return to their previous employer, 16 and supportive employers have been recognised as promoting employment in this population. 24 Early vocational intervention could preserve this relationship and maximise employer support through liaison with the employer and use of appropriate workplace supports.…”
Section: Early Interventionmentioning
confidence: 99%
“…Employment rate has traditionally been used as the primary outcome measure of both return to work (RTW) programmes post-SCI research investigating this area. [7][8][9][10] Employment rate differs broadly between countries due to different cultural, economic and legislative environments, with estimates ranging between 15 and 60%. 5 Recent literature regarding Australian employment rates for people who have sustained a SCI estimates median RTW rates between 21 and 35%, compared with a general workforce participation rate of 65%.…”
Section: Spinal Cord Injury and Employmentmentioning
confidence: 99%
“…Notwithstanding the challenges and disincentives, most people with SCI report being motivated to work (Bergmark, Westgren, andAsaba 2011, 2556;Krause and Reed 2011, 288). The factors most likely to translate this hope into reality include the level of education, the severity of injury, and whether or not a person is able to return to their former employer (Krause et al 2010, 487).…”
Section: The Cold Hard Factsmentioning
confidence: 99%
“…. I have never had much of a head for studying and never liked reading and such' (see Bergmark, Westgren, andAsaba 2011, 2556). Even so-called white-collar employment presents a challenge, whether or not pre-injury skills 'suit' people with SCI.…”
Section: The Cold Hard Factsmentioning
confidence: 99%
“…Identified barriers include transportation, health complications related to SCI, perceived discrimination in the work environment, lack of private insurance coverage, and loss of financial benefits. [1][2][3][4] Predictors of employment include being male, having higher education, having higher motivation, being younger at the time of SCI, having lived for more years with SCI, and having been employed before the SCI. 2,3,5 Demographic and injury variables only explain 30% of variance in employment 2 ; therefore, more research on facilitators and barriers to employment is needed.…”
mentioning
confidence: 99%